Kontribusi Al-Makmun dalam Transmisi Filsafat Aristotelian ke Dunia Islam Melalui Penerjemahan Buku-Buku Yunani di Bawah Kekhalifahan Abbasiyah - Farhan Al Fuadi Farhan (SiRad: Pelita Wawasan, 2025)
The transmission of Aristotelian philosophy to the Islamic world through the translation of Greek texts into Arabic had a profound influence on philosophy, science, and Islamic theology (kalam). This study aims to examine the historical process of translating texts originating from Greek culture into Arabic, either directly or through the intermediary of Syriac. As is well known, the translation of these works gave rise to the development of philosophical, scientific, and theological traditions within the Islamic intellectual environment during the Abbasid Caliphate, particularly during the reign of al-Ma'mun. Using a qualitative historical analysis method based on primary sources especially al-Fihrist by Ibn al-Nadim this article reconstructs the mechanisms and key figures involved in the transmission process. The analysis reveals that the translation movement was not merely a passive transfer of knowledge but rather a complex project driven by the political patronage of the caliphate, mediated by Syriac-speaking translators, and institutionalized through establishments such as the Bayt al-Hikmah (House of Wisdom). As a result of this transmission of Aristotelian philosophical traditions, we highlight figures such as al-Kindi and al-Farabi, who are recognized as important representatives of the first generation of Muslim philosophers. They contributed significantly by translating, commenting on, summarizing, and reviewing philosophical texts to facilitate philosophical education among Muslim scholars. Hence, al-Farabi came to be known as the “Second Teacher,” with Aristotle regarded as the “First Teacher”. [Transmisi filsafat Aristotelian ke dunia Islam melalui kegiatan penerjemahan buku-buku Yunani ke dalam bahasa Arab memiliki pengaruh besar terhadap filsafat, sains dan kalam. Penelitian ini berusaha mengkaji proses historis penerjemahan buku-buku yang berasal dari kebudayaan Yunani ke dalam bahasa Arab baik langsung atau melalui bahasa Suryani. Sebagaimana kita ketahui, dari proses penerjemahan buku-buku ini, tradisi filsafat, sains dan kalam berkembang dalam lingkungan intelektual Islam di era kekhalifahan Abbasiyah, terutama era al-Makmun. Dengan menggunakan metode analisis historis-kualitatif terhadap sumber primer, terutama al-Fihrist karya Ibnu Nadim, artikel ini merekonstruksi mekanisme dan aktor kunci dalam proses transmisi tersebut. Hasil analisis menunjukkan bahwa gerakan penerjemahan bukan sekadar transfer pengetahuan pasif, melainkan sebuah proyek kompleks yang didorong oleh patronase politik kekhalifahan, dimediasi oleh para penerjemah berbahasa Suryani, dan dilembagakan melalui institusi seperti Bayt al-Hikmah. Sebagai buah dari transmisi tradisi filsafat Aristotelian, kami merujuk pada al-Kindi dan al-Farabi yang diakui sebagai tokoh penting dari kelompok filosof muslim pertama yang berajasa dalam usaha penerjemahan dan menyusun komentar-komentar, ringkasan serta ulasan singkat yang berguna bagi pengajaran filsafat kepada para sarjana muslim. Sehingga al-Farabi disebut “Guru Kedua”dan Aristoteles adalah “Guru Pertama”nya.]